Fatigue growth rate of inclined surface cracks in aluminum and titanium alloys - R.R. Yarullin; M.M. Yakovlev (Fracture and Structural Integrity)
In this paper the fatigue crack growth tests were carried out on surface-crack tension (SCT) specimens, made of 7050 and Ti6Al4V alloys, with initial semi-elliptical surface cracks. Pure Mode I conditions were realized on SCT specimens with crack plane located orthogonal to the loading direction, while Mixed-mode conditions were observed on SCT specimens with inclined crack. Optical microscope measurements and the crack mouth opening displacement (CMOD) method were respectively used to monitor crack length and calculate crack depth. Current crack shape during the tests was highlighted by alternation of loading spectrum with baseline load block and a marker load block. The stress strain field along the crack front of semi-elliptical cracks in the SCT specimens was assessed by Finite Element Method (FEM) analysis. The stress intensity factors (SIFs) were calculated along crack fronts and equivalent elastic SIF formulation was used for crack growth rate assessment under mixed mode conditions. As a result, the fracture resistance parameters of aluminum and titanium alloys were obtained for two crack propagation directions under Mode I and Mixed-mode loading. The benefits of using the computational and experimental results of SCT specimen for the assessment of the surface crack growth rate in aluminum and titanium alloys under Mixed-mode loading conditions were stated.